2017
DOI: 10.1016/j.ejvs.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Renal Complications between Endografts with Suprarenal and Infrarenal Fixation

Abstract: Objectives Surgeons have multiple grafts options available for the endovascular treatment of abdominal aortic aneurysms (EVAR), and some hypothesize that suprarenal fixation endografts may result in higher rates of renal complications than infrarenal endografts. This study aims to compare the outcomes of contemporary suprarenal and infrarenal endografts. Methods The Targeted Vascular Module of the National Surgical Quality Improvement Project was utilized to identify patients undergoing EVAR for infrarenal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
(36 reference statements)
0
15
0
1
Order By: Relevance
“…This type of proximal fixation has previously been implicated in the pathogenesis of renal injury in EVAR and this may affect the generalisation of the findings. 35,36 However, suprarenal fixation was not an inclusion criterion and this population reflects contemporary EVAR practice. As far as contrast volumes are concerned, this pilot study was not designed to assess the impact of baseline risk factors on subsequent AKI development.…”
Section: Limitationsmentioning
confidence: 99%
“…This type of proximal fixation has previously been implicated in the pathogenesis of renal injury in EVAR and this may affect the generalisation of the findings. 35,36 However, suprarenal fixation was not an inclusion criterion and this population reflects contemporary EVAR practice. As far as contrast volumes are concerned, this pilot study was not designed to assess the impact of baseline risk factors on subsequent AKI development.…”
Section: Limitationsmentioning
confidence: 99%
“…Four additional studies on this subject were published in 2017, with the study by Zetterval et al looking at 3587 patients in the American National Surgical Quality Improvement Project undergoing EVAR from 2011 to 2013, providing the most contemporaneous dataset. 17 They found that after adjustment, SR grafts had significantly higher rates of renal complications compared with IR (OR 12.0; 95% CI 1.6e91) and length of stay > 2 days (OR 1.4; 95% CI 1.2e1.7); however, this study is limited by the very short-term nature of the results, and no reporting of any additional outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…On a positive note, a large number of patients were available to help answer the study aims: 3587 collected from a contemporary 3 year period using modern day endografts. 1 However, the study also highlights some of the limitations of large registry data sets. The overall low rate of renal complications described in this study is not in keeping with contemporary literature, 6 where rates of renal injury of up to 20% have been reported.…”
mentioning
confidence: 87%
“…In this issue, Zetterval et al suggest a significantly greater risk of renal complications after endovascular aneurysm repair (EVAR) with suprarenal fixation, based on an analysis of a large cohort of patients with abdominal aortic aneurysm (AAA), drawn from the National Surgical Quality Improvement Project (NSQIP) in North America. 1 Renal injury following endovascular AAA repair is well recognised, 2 and there is increasing anxiety regarding the longer-term impact of EVAR on renal function. 3 Concerns that acute kidney injury (AKI) after EVAR may be greater for patients treated with endografts with suprarenal fixation are not new.…”
mentioning
confidence: 99%